“Existences holding hands”: Winterson retelling Shakespeare (Altre Modernità, 2017)
To celebrate the 400th anniversary of Shakespeare's death,The Hogarth Press inaugurated The Hogarth Shakespeare project, which sees Shakespeare's works retold by acclaimed and bestselling novelists of today. The first volume of the series to appear was Jeanette Winterson's "The Gap of Time" (2015), a cover version of "The Winter's Tale". Winterson considers it a "talismanic text" for her,in part because it is a play about a foundling, and Winterson is one. But "The Winter's Tale" is also a play about forgiveness, a theme which has always been dear to Winterson, who wrote about it in "Why Be Happy When You Could Be Normal?" (2011).The paper aims to underline such aspects in her rewriting of Shakespeare's play, together with the theme of time, fundamental to both Shakespeare and Winterson. Time is indeed among the protagonists of "The Winter's Tale", which can be read as a "meditation on time" (Lombardo 2004), so much so that time is embodied as a speaking character in the Chorus. "Time is reversible", declares Winterson in her cover version; time redeems and can be redeemed, Shakespeare seems to suggest in "The Winter's Tale"."The Gap of Time" completes a retelling of such themes that Winterson started back in 1989 with her novel "Sexing the Cherry", in which she claimed that parallel lives, made of the alternative decisions not taken in the past, go on living so as to create an alternative present, which is what happens in "The Winter's Tale".